(untitled) (Nigerian Dental Journal, 2010)
Plasma cell neoplasms (multiple myeloma, solitary plasmocytoma of bone and extra medullar plasmocytoma) are characterized by a monoclonal neoplastic proliferation of plasma cells. Multiple myeloma is a monoclonal malignant proliferation of plasma cells that causes osteolytic lesions in the vertebrae, ribs, pelvic bone, skull and jaw. We report a case of a 69-year-old male patient who presented with a tumefaction in the body of mandible, which had evolved over the previous two months. In the radiographic examination, an extensive osteolytic lesion was observed in the body of mandible. An incisional biopsy was performed and histopathological study revealed a malignant hematopoietic neoplasm formed by plasmacytoid cells. Knowledge about the maxillofacial manifestations of multiple myeloma is important for the early diagnosis of the disease, since its primary form can manifest itself in the jaw.